An Empirical Investigation of Factors Affecting the Compulsory of Personal Income Tax on Personal Information Tax Services Pratama, West Medan - Yunita Sari Rioni (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The purpose of this study was to investigate the influence of awareness of paying tax, knowledge and understanding of the tax rules, service quality of tax office, modernization of tax administration system, and administrative sanction for the compliance level of individual taxpayers. This study used primary data and the population of this study was 124.872 individual taxpayers in the office of Pratama Tax Service West Medan. The sample in this study were selected through Slovin formula. The data processed through multiple regression model. The result of F-test showed that awareness of paying tax, knowledge and understanding of the tax rules, service quality of tax office, modernization of tax administration system, and administrative sanction have the significant influence on the compliance level of individual taxpayers, simultaneously. However, the result of t-test showed that awareness of paying tax, service quality of tax office, and administrative sanction have the significant influence on the compliance level of individual taxpayers, partially. Meanwhile, the knowledge and understanding of the tax rules, and modernization of tax administration system did not have influence on the compliance level of individual taxpayers.